A regência variável do verbo de movimento ir na cidade de Vitória-ES - Citeli, Bárbara Gomes (2017)
Based on the theoretical approaches proposed by Variationist Sociolinguistics, this study consists of the analysis of the variation among the regent prepositions of the verb “ir” with the meaning of movement “a, para e em”, which are present in the talk of residents of the city of Vitoria, located in the state of Espírito Santo. For the development of this research, forty-six interviews were analyzed that make up the sample PortVix "Portuguese spoken in the city of Vitoria”. Initially we consider the hypothesis that this phenomenon does not occur in a random way and that the preposition “em”,, considered a non-standard form by normative grammars occurs more frequently in the speech data, since this preposition is being more and more used by the speakers of Portuguese language. Due to this, we try to investigate which linguistic and extralinguistic factors contribute to this variation, by statistically analyzing the data through the GoldVarb X computer program (SANKOFF; TAGLIAMONTE; SMITH, 2005) and later we compare the results obtained with the research carried out on the Same phenomenon with different samples of Brazilian Portuguese. The results showed that the preposition”para” is the most used as the main regent of the verb of movement “ir” by the informants of the Speech Capixaba community, followed by the prepositions “em” and “a”. In addition to this, we found out that the linguistic variables Degree of Definiteness, Spatial Configuration and Speech Narrativity and social variables Age Range and Schooling were significant in relation to the variable regency of the movement verb “ir”, since they were selected as statistically relevant for the Phenomenon analyzed. It should also be noted that the present study contributes to the discussions about the phenomenon of variation in the regency of the verb of movement “ir”, because it launches new discussions about this phenomenon and compares its performance in different parts of Brazil.